DESKRIPSI KEMAMPUAN PENALARAN MATEMATIS SISWA DITINJAU DARI GAYA BELAJAR DAN GENDER - Nurhayati, Eti; Subekti, Fitrianto Eko (AlphaMath : Journal of Mathematics Education, 2017)
The objectives of this research was to construct description on student’s mathematicalcognitive ability in SMP Muhammadiyah Sumbang viewed from learning style and gender ontopic of rectangular. The research method was descriptive qualitative. The researchpopulation was students of 7th Grade A and D with purposive sampling technique. Studentswere divided into six groups and two students from each group were selected as respondents.Test, interview and documentation were used as the data collection. The results indicated: 1)Male and female students with visual learning style could not have knowledge of fiveindicators of mathematical cognitive ability as follow: to propose presumption, to makemathematical manipulation, to draw conclusions, to construct evidence, to give reasonableevidence for solutions, to examine argument validity, and to find path of mathematicalindication. 2) Male and female students with auditory learning style could have knowledgeone indicator of mathematical cognitive ability as of to find path of mathematical indication.3) Male students with kinesthetic learning style could have knowledge of one indicator ofmathematical cognitive ability as of to make mathematical manipulation. 4) Female studentswith kinesthetic learning style could have knowledge of one indicator of mathematicalcognitive ability as of to propose presumption.KEY WORDS: Mathematical cognitive ability, Learning style, Gender